'The day after': Exit-induced legal lacuna. Issue 2 (April 2017) - Nicolaides, Phedon
The purpose of the two-year rule in Article 50 TEU is to prevent the remaining Member States from delaying the exit of the withdrawing Member State through stalling tactics. This article argues that the two-year period is a double-edge sword. It affords very little time to the withdrawing Member State to adjust its domestic legislation, regulatory system and administrative structure to be able to function effectively on the day after exit from the EU. The UK's Great Repeal Bill proposes a 'copy and paste' approach. However, this approach is only a partial solution to the problem of the 'exit-induced' legal lacuna. With the use of two case studies, the article demonstrates that the UK will have to establish new regulatory procedures and redefine EU concepts inserted in national law. The UK will 'regain control' but will have to follow EU practice. At some point in the future it will also encounter the dilemma of diverging from EU practice and creating two sets of compliance standards for its companies.